Simulation study of two-dimensional viscoelastic imaging of soft tissues using the extended Kalman filter for tumor detection. (May 2020) - Luong, Quang-Hai; Tran, Duc-Tan; Trung, Nguyen Linh; Huynh, Huu Tue; Do, Minh N
The mechanical properties of tissues in terms of elasticity and viscosity provide useful information for tumor detection. Recently, shear wave imaging has been developed to quantify tissue elasticity by estimating the parameters of the complex shear modulus (CSM). The current challenges of CSM estimation are estimation accuracy, computational complexity, and dealing with heterogeneous media. In this paper, we propose a two-dimensional CSM imaging method based on the extended Kalman filter (EKF). Firstly, particle velocities at spatial locations are acquired by using a Doppler ultrasound system. Then, the EKF is used to estimate the CSM at each spatial point, and hence for an area of interest using ray scanning. Finally, the CSM images are also enhanced using several image processing algorithms. Simulated experiment and performance studies are carried out to confirm the quality of the proposed method.